Measurement of the ultrasonic diffusion coefficient in a resonant multiple scattering suspension. Issue 1 (January 2021) - Delmotte, Fanambinana; Brunet, Thomas; Clisson, Gérald; Leng, Jacques
Abstract: We report on frequency-resolved experimental measurements of the ultrasonic diffusivity in the MHz range. By means of robotics, we produced a highly monodisperse suspension made of soft metallic micro-beads randomly-dispersed in a water-based gel-matrix. The measured diffusion coefficient is shown to vary significantly with frequency by more than one order of magnitude that is probably due to the sharp scattering resonances of the metallic particles.